Pretreatment biopsy for histological diagnosis and induction therapy in thymic tumors - Yue, Jie; Gu, Zhitao; Yu, Zhentao; Zhang, Hongdian; Ma, Zhao; Liu, Yuan; Fang, Wentao; Research of Thymomas, Members of the Chinese Alliance for (Journal of Thoracic Disease; Vol 8, No 4 (April 01, 2016): Journal of Thoracic Disease [Thymic Malignancy—Perspectives from the Chinese Alliance for Research in Thymomas (ChART)], 2016)
Background: This study was to investigate the value of pretreatment biopsy for histological diagnosis and induction therapies in the mnagement of locally advanced thymic malignancies. Methods: The clinical pathological data of patients with thymic tumors in the Chinese Alliance for Research in Thymomas (ChART) who underwent biopsy before treatment from 1994 to December 2012 were retrospectively reviewed. The application trend of preoperative histological diagnosis and its influence on treatment outcome were analyzed. Results: Of 1,902 cases of thymic tumors, 336 (17.1%) had undergone biopsy for histological diagnosis before therapeutic decision was decided. In recent years, percentage of pretreatment histological diagnosis significantly increased in the later ten years than the former during the study period (P=0.008). There was also a significant increase in thoracoscopy/mediastinoscopy/E-BUS biopsy as compared to open biopsy (P=0.029). Survival in Patients with preoperative biopsy for histology had significantly higher stage lesions (P=0.000) and higher grade malignancy (P=0.000), thus a significantly lower complete resection rate (P=0.000) and therefore a significantly worse survival than those without preoperative biopsy (P=0.000). In the biopsied 336 patients, those who received upfront surgery had significantly better survival than those received surgery after induction therapy (P=0.000). In stage III and IVa diseases, the R0 resection rate after induction therapies increased significantly as compared to the surgery upfront cases (65.5% vs. 46.2%, P=0.025). Tumors downstaged after induction had similar outcomes as those having upfront surgery (92.3% vs. 84.2%, P=0.51). However, tumors not downstaged by induction had significantly worse prognosis than those downstaged (P=0.004), and fared even worse than those having definitive chemoradiation without surgery (37.2% vs. 62.4%, P=0.216). Conclusions: It is crucial to get histological diagnosis for thymoma before surgery or adjuvant treatment and minimally invasive biopsy should be undertaken. Although in our study we could not find the benefit of induction chemotherapy before surgery in survival and recurrence rate, it could increase the R0 resection rate compared with direct surgery in late stage (III and IVa).